Perception, participation and empowerment among participants of afforestation programe in Toshia, Nigeria - Geidam, Alhaji Abdu (2012)
This thesis focuses on community development among the participants of afforestation programme in Toshia, Nigeria. The general objectives of this study were to explore how participation in afforestation programme influences empowerment among the participants. The specific objectives of this study were to measure the levels of perception, the level of participation and empowerment of the participants of the afforestation programme; to describe the level of perception, level of participation and level of empowerment, and finally to examine the relationship between the perception, participation and empowerment with age, ethnicity and level of education. Data was collected from 150 respondents using purposive sampling technique and discussions with participants of the afforestation programme were also used to gather data. Pearson correlation, ANOVA (Analysis of Variance) and multiple linear regression analysis were used to examine the association between the variables. In this study, the findings revealed that the levels of perception, participation and empowerment were at medium range. The analysis reveals that there was a significant correlation between the level of perception (F=42.420, r= 0.464, p=0.00, the level of participation (F=17.013, r = 0.488, p=0.00 and the level of empowerment of the participants. The participants perception and participation contributed about 39.4 % (R2 = .394) in explaining the variation of empowerment. The finding of this study showed that the participation of the respondents in the afforestation program had led to their empowerment. Therefore special considerations should be given to the participants and effort should always be made to improve upon them through engaging competent leader who are well qualified in the field of afforestation to manage the affairs, equipping the programme with facilities, enhancing community participation and finally providing seedlings that are drought resistance.